Debating Vivekananda: a reader - Raghuramaraju, A. (Oxford University Press, 2014)
section I. Extent and limits of impact -- section II. Practical Vedanta -- section III. Ramakrishna Paramahansa -- section IV. Secularism -- section V. Fundamentalism -- section VI. Woman -- section VII. Science